Representasi Gaya Hidup Modern dalam Media Sosial Instagram @tantrinamirah - Zulfa Triwahyuningsih; Said Romadlan; Wininda Qusnul Khotimah (Jurnal Dakwah dan Komunikasi, 2022)
Modern lifestyle is an attitude, personality, and what of the behaviors that correspond with the demands of the developments of the times. This occurred because of an awareness of man within him to keep on studying in the middle of the development of the world. The research ia a culturalstudies to uncover the representasion of modern lifestyle as popular culture. In which this case, a culture that is featured in popular culture instagram accounts is habitual activities that can be enjoyed by all men were fashion, care of the body and interests that become their needs. What was used in the study is a methodological analysis logician Ferdinand de Saussure to display lifestyle forms of modern in instagram @tantrinamirah account, through signifier and signified in the instagram account. The results of research on lifestyle modern ini social media instagram @tantrinamirah, find the the form of modern lifestyle which includes fashion, the choice of food and drink, the tourist area of the hobbies and grocery products. The factors that determine lifestyle modern in social media instagram @tantrinamirah, of them: the image of themselves, consisting of a style of dress is fashionable, a healty lifestyle, interest in exclusivity culture and the factors. There is also the ideology of the practices, with this incidence of these signs in stuff used their phenomena and into a theme in the community. To create a culture consumer, in which content word that continues to displayed will affect the act of. The use of branded become a legal attitude on fashion, that shows their interest in product fancy.